Hematological changes and cytogenotoxicity in the tilapia Oreochromis niloticus caused by sub-chronic exposures to mercury and selenium - Seriani, Robson; Franca, Jakeline Galvão [UNESP]; Lombardi, Julio Vicente; Brito, Jôse Mara; Tavares Ranzani-Paiva, Maria José (Springer, 2015)
Fish bioassays are valuable tools that can be used to elucidate the toxicological potential of numerous substances that are present in the aquatic environment. In this study, we assessed the antagonistic action of selenium (Se) against the toxicity of mercury (Hg) in fish (Oreochromis niloticus). Six experimental groups with six fish each were defined as follows: (1) control, (2) mercury (HgCl2), (3) sodium selenite (Na2Se4O3), (4) sodium selenate (Na2Se6O4), (5) mercury + sodium selenite (HgCl2 + Na2Se4O3), and (6) mercury + sodium selenate (HgCl2 + Na2Se6O4). Hematological parameters [red blood cells (RBC), white blood cells (WBC), and erythroblasts (ERB)] in combination with cytogenotoxicity biomarkers [nuclear abnormalities (NAs) and micronuclei (MN)] were examined after three, seven, ten, and fourteen days. After 7 days of exposure, cytogenotoxic effects and increased erythroblasts caused by mercury, leukocytosis triggered by mercury + sodium selenite, leukopenia associated with sodium selenate, and anemia triggered by mercury + sodium selenate were observed. Positive correlations that were independent of time were observed between WBC and RBC, ERB and MN, and NA and MN. The results suggest that short-term exposure to chemical contaminants elicited changes in blood parameters and produced cytogenotoxic effects. Moreover, NAs are the primary manifestations of MN formation and should be included in a class characterized as NA only. Lastly, the staining techniques used can be applied to both hematological characterization and the measurement of cytogenotoxicity biomarkers.
Keywords: Toxicity; Mercury; Selenium; Hematology; Nuclear abnormalities; Micronuclei